Strategies to maintain fitness during periods of inactivity (P360Performance, 2020)
Periods of reduced training, or stopping all together, can lead to a reduction in fitness. This is related to the principle of training reversibility, where positive physiological adaptations in response to training will be partially or completely reversed, reducing athletic performance (1). The reduction in aerobic fitness that inevitably occurs will be inversely related to the aerobic training load accumulated before the period of reduced training, similar with strength training.